Carbon nanotube loaded ferronickel phytate OER catalyst and preparation method thereof
The preparation of carbon nanotube-supported nickel-ferrous phytate OER catalysts through a one-step co-precipitation method has solved the problems of long preparation time and low catalytic activity in the prior art, and achieved efficient and low-cost catalyst preparation and significantly improved OER activity.
Patent Information
- Application Number
- CN202510101552.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The preparation of existing OER catalysts takes a long time, consumes a large amount of energy and has low catalytic activity, which limits its application.
Through a simple and efficient one-step co-precipitation method, a nickel-ferrous phytate OER catalyst supported by carbon nanotubes was prepared, and carbon nanotubes were used to enhance conductivity and provide growth space. The nickel-ferrous phytate nanoparticles were loaded on the carbon nanotubes and had photothermal response characteristics.
It realizes efficient and low-cost catalyst preparation, has high OER activity, and significantly improves OER activity under near-infrared light and reduces overpotential.
Smart Images

Figure CN119733569A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a carbon nanotube-supported nickel-iron phytate OER catalyst and a preparation method thereof. Background Art
[0002] Hydrogen energy is a promising energy carrier, and electrocatalytic water splitting is one of the effective strategies to obtain sustainable green hydrogen energy, including the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). However, OER involves a four-electron transfer process, which requires high energy to overcome the slow reaction kinetics, greatly limiting the energy conversion efficiency of electrochemical water splitting. Currently, Ru and Ir-based materials have high OER activity, but their scarcity and high cost hinder their widespread application. Therefore, it is imperative to design and manufacture cost-effective and high-performance OER electrocatalysts.
[0003] Transition metal phosphates have flexible coordination characteristics, which can effectively stabilize the intermediate state of the active center. At the same time, the phosphate group can also act as a proton acceptor to accelerate proton conductivity. It is one of the most promising OER catalysts. However, its long preparation time and high temperature treatment cause excessive energy consumption, and its low catalytic activity limits its application. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a carbon nanotube-loaded nickel iron phytate OER catalyst and a preparation method thereof. The carbon nanotube-loaded nickel iron phytate OER catalyst is prepared by integrating doping regulation through a simple and efficient one-step co-precipitation method. The preparation method is simple and can be prepared at room temperature. The prepared catalyst has high OER activity. Moreover, since the catalyst has the characteristics of photothermal response, its OER activity can be further significantly improved under near-infrared light.
[0005] The present invention is specifically implemented through the following technical solutions.
[0006] The present invention provides a method for preparing a carbon nanotube-supported nickel-iron phytate OER catalyst, comprising the following steps: A mixed solution of soluble nickel salt, soluble iron salt and carbon nanotubes is prepared by using water as a dispersion medium.
[0007] The sodium phytate aqueous solution is mixed with the mixed solution, and the complexation is stirred at room temperature. The nickel-iron phytate nanoparticles generated during the complexation process are loaded on carbon nanotubes to obtain a carbon nanotube-loaded nickel-iron phytate OER catalyst. Both phytic acid and its sodium salt have strong metal chelating ability, but the acidity and alkalinity of their aqueous solutions are quite different; the phytic acid aqueous solution is acidic, while the phytic acid sodium salt aqueous solution is alkaline. The present invention uses phytic acid sodium salt.
[0008] Preferably, the amount of Ni element used is 70% to 90% of the total molar amount of Ni and Fe, and more preferably 80%.
[0009] Preferably, in the mixed solution, the total amount of soluble nickel salt and soluble iron salt and the amount of carbon nanotubes are in a ratio of 0.01g to 0.02g: 1mg to 2mg. More preferably, the soluble nickel salt and the soluble iron salt are dissolved in water to obtain a mixed salt solution, and the mixed salt solution is evenly mixed with an aqueous dispersion of carbon nanotubes under stirring to obtain a mixed solution. The solid-liquid ratio of the total amount of soluble nickel salt and soluble iron salt to water is 0.02g to 0.04g: 1mL, more preferably 0.03g: 1mL; the concentration of the aqueous dispersion of carbon nanotubes is 1mg / mL to 2mg / mL, more preferably 1.5mg / mL, and the volume ratio of the mixed salt solution to the aqueous dispersion of carbon nanotubes is 1:2.
[0010] Preferably, the molar ratio of sodium phytate: the total amount of Ni and Fe is 1:2-3, more preferably 1:2.5.
[0011] Preferably, the stirring complexation time is 0.5 h to 1.5 h, more preferably 1 h.
[0012] Preferably, the soluble nickel salt and the soluble iron salt are corresponding nitrates.
[0013] Preferably, when the mixed solution is prepared, the stirring time is 5 minutes.
[0014] Preferably, after the complexation reaction is completed, centrifugation, washing and drying are performed, the drying temperature is 60° C., and the drying time is 12 hours.
[0015] The present invention provides a carbon nanotube-supported nickel-iron phytate OER catalyst prepared by the above-mentioned preparation method. The carbon nanotubes are interconnected and entangled, and the surface of the carbon nanotubes is loaded with nickel-iron phytate nanoparticles, and the average diameter of the nickel-iron phytate nanoparticles is 30nm. The carbon nanotubes provide more growth space for the particles, expose more active sites, and the carbon nanotubes can enhance the conductivity of nanomaterials. The rich functional groups on the surface of the carbon nanotubes adsorb metal ions through electrostatic mutual attraction, and then the multiple complexing sites of the phytate enable it to bind different metal ions in one or more ligands, further enhancing the synergistic effect between metals.
[0016] The present invention provides an oxygen evolution reaction electrocatalyst, which is the above-mentioned carbon nanotube-loaded nickel iron phytate OER catalyst. The nickel phytate and carbon nanotubes in the carbon nanotube-loaded nickel iron phytate nanomaterial of the present invention have significant photothermal response characteristics, significantly increase the local surface temperature under near-infrared light, promote interfacial charge transfer and accelerate reaction kinetics; the photothermal effect is further enhanced by adjusting the coordination structure through the introduction of iron. Under near-infrared irradiation, light energy is directly converted into heat energy, so that the OER overpotential is significantly reduced, which is attributed to the offset of endothermic enthalpy change and the reduction of OER activation energy. This application can be extended to other OER catalysts with photothermal effect.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses a water-soluble dispersion medium to first prepare a mixed solution containing a soluble nickel salt, a soluble iron salt and carbon nanotubes, then mixes a phytic acid sodium salt aqueous solution with the mixed solution, stirs and complexes at room temperature, and loads the nickel-iron phytate nanoparticles generated during the complexation process on the carbon nanotubes to obtain a carbon nanotube-loaded nickel-iron phytate OER catalyst. The preparation method of the present invention adopts a simple one-step coprecipitation method at room temperature, does not require special equipment, has low cost, can be expanded on a large scale, has high repeatability, and has broad prospects for industrial application.
[0018] The carbon nanotube-loaded nickel-iron phytate nanomaterial prepared by the present invention has relatively excellent OER performance, and because the catalyst has the characteristics of photothermal response, its OER activity can be further significantly improved under near-infrared light. For example, under near-infrared light irradiation, it can reach 1000mA cm -2 The current density is only 285 mV. The near-infrared light irradiation offsets the endothermic enthalpy change and reduces the activation energy of OER, significantly improving the OER performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the XRD pattern of the catalyst sample prepared in Example 1 of the present invention.
[0020] Figure 2 This is the SEM image of the catalyst sample prepared in Example 1 of the present invention.
[0021] Figure 3 This is a TEM image of the catalyst sample prepared in Example 1 of the present invention.
[0022] Figure 4 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Example 1 of the present invention in 1M KOH solution.
[0023] Figure 5This is a linear sweep voltammogram of OER of the catalyst sample prepared in Example 1 of the present invention under near-infrared light irradiation, wherein the near-infrared light intensity gradually increases from (a) to (e).
[0024] Figure 6 This is the SEM image of the catalyst sample prepared in Comparative Example 1 of the present invention.
[0025] Figure 7 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Comparative Example 1 of the present invention in 1M KOH solution.
[0026] Figure 8 This is the SEM image of the catalyst sample prepared in Comparative Example 2 of the present invention.
[0027] Fig. 9 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Comparative Example 2 of the present invention in 1M KOH solution.
[0028] Fig.10 Linear sweep voltammograms of OER in 1 M KOH solution for catalyst samples prepared for different Ni / Fe metal ratio ranges.
[0029] Fig.11 Linear sweep voltammograms of OER in 1 M KOH solution for catalyst samples prepared for different concentration ranges of carbon nanotube aqueous dispersions.
[0030] Fig.12 Linear sweep voltammograms of OER in 1 M KOH solution for catalyst samples prepared for a range of phytate to metal salt ratios.
[0031] Fig.13 Linear sweep voltammograms of OER in 1 M KOH solution for the catalyst samples prepared for the time range of stirring complexation. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0033] In order to solve the problems that the preparation of the current OER catalyst takes a long time and the high temperature treatment causes excessive energy consumption, and the poor conductivity and low catalytic activity limit its application, the present invention provides a method for preparing a carbon nanotube-supported nickel-iron phytate nanomaterial, comprising the following steps: A soluble nickel salt and a soluble iron salt are dissolved in water to obtain a mixed salt solution, and the mixed salt solution is evenly mixed with an aqueous dispersion of carbon nanotubes under stirring to obtain a mixed solution.
[0034] Sodium phytate is dissolved in water, added to the mixed solution, and stirred at room temperature for complexation. The nickel-iron phytate nanoparticles generated during the complexation process are loaded on carbon nanotubes to obtain nickel-iron phytate nanomaterials loaded on carbon nanotubes. The structure of the nickel-iron phytate nanomaterial loaded on carbon nanotubes is that the carbon nanotubes are interconnected and entangled, and nickel-iron phytate nanoparticles with an average diameter of about 30nm are modified on the surface of the carbon nanotubes; the carbon nanotubes provide more growth space for the particles and expose more active sites. At the same time, the carbon nanotubes can enhance the conductivity of the nanomaterial. The rich functional groups on the surface of the carbon nanotubes adsorb metal ions through electrostatic attraction, and then the multiple complexation sites of the phytate enable it to bind different metal ions in one or more ligands, further enhancing the synergistic effect between metals.
[0035] The present invention is specifically described below by the following examples and comparative examples.
[0036] Example 1 (1) Add 30 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonic to form a uniform carbon nanotube dispersion.
[0037] (2) Dissolve 0.8 mM nickel nitrate hexahydrate and 0.2 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0038] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0039] (4) Dissolve 0.4 mM sodium phytate in 10 mL of deionized water and stir to form a uniform solution; (5) Add the sodium phytate solution into the mixed solution in (3) and stir for 1 hour.
[0040] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0041] The OER reaction performance test of the carbon nanotube-supported nickel-iron phytate nanomaterial prepared in Example 1 is as follows: Weigh 2.5 mg of the catalyst sample (the catalyst prepared in Example 1 of the present invention, hereinafter referred to as the catalyst sample) and add it to a solution containing 480 μL of isopropanol and 20 μL of Naifon solution (5 wt%), and ultrasonically treat for 30 min to evenly disperse the catalyst. Take 5 μL of the evenly dispersed sample solution to the surface of the glassy carbon electrode, dry it, and test it using a standard three-electrode system, with a graphite rod as the counter electrode, mercury / mercuric oxide as the reference electrode, and 1 M KOH as the electrolyte. The scan rate of the linear voltammetric curve is 5 mV / s.
[0042] Test results: Figure 4 As shown, when 20 mA·cm -2 At a current density of , the overpotential is 245mV.
[0043] Considering that both nickel phytate and carbon nanotubes have excellent photothermal effects, the carbon nanotube-loaded nickel iron phytate nanomaterial prepared in this embodiment was further tested for its OER performance under near-infrared light irradiation. As the near-infrared light intensity increases, that is, the near-infrared light intensity gradually increases from (a) to (e), the carbon nanotube-loaded nickel iron phytate nanomaterial prepared in this embodiment shows a gradually decreasing overpotential, such as Figure 5 As shown, the maximum light intensity reaches 1000mA·cm -2 The current density is only 285mV. This is attributed to the fact that under near-infrared irradiation, light energy is directly converted into heat energy, which promotes interfacial charge transfer and accelerates reaction kinetics, thereby improving OER performance.
[0044] Comparative Example 1 (1) Add 30 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonic to form a uniform carbon nanotube dispersion.
[0045] (2) Dissolve 1 mM nickel nitrate hexahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0046] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0047] (4) Dissolve 0.4 mM sodium phytate in 10 mL of deionized water and stir to form a homogeneous solution.
[0048] (5) Add the sodium phytate solution into the mixed solution in (3) and stir for 1 hour.
[0049] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0050] The OER reaction performance test was performed on the carbon nanotube-loaded nickel-iron phytate nanomaterial prepared in Comparative Example 1, and the specific implementation method was the same as that in Example 1.
[0051] Test results: Figure 7 As shown, when 20 mA·cm -2 When the current density is , the overpotential is 377mV. Compared with Example 1, Comparative Example 1 does not introduce iron, and the overpotential increases.
[0052] Comparative Example 2 (1) Add 30 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonic to form a uniform carbon nanotube dispersion.
[0053] (2) Dissolve 1 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a homogeneous solution.
[0054] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0055] (4) Dissolve 0.4 mM sodium phytate in 10 mL of deionized water and stir to form a homogeneous solution.
[0056] (5) Add the sodium phytate solution into the mixed solution in (3) and stir for 1 hour.
[0057] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0058] The OER reaction performance test was performed on the carbon nanotube-loaded nickel-iron phytate nanomaterial prepared in Comparative Example 2, and the specific implementation method was the same as that in Example 1.
[0059] Test results: Fig. 9 As shown, when 20 mA·cm -2 When the current density is , the overpotential is 452mV. Compared with Example 1, Comparative Example 2 does not introduce nickel, and the overpotential increases.
[0060] Figure 1 This is the XRD pattern of the catalyst sample prepared in Example 1 of the present invention. Figure 1 It can be seen that no obvious diffraction peak was observed, indicating that the prepared nanomaterial was an amorphous structure; the broad diffraction peak at around 26° was attributed to the presence of carbon nanotubes.
[0061] Figure 2 This is a SEM image of the catalyst sample prepared in Example 1 of the present invention. Figure 2 It can be seen that the structure of the prepared nanomaterial is that the carbon nanotubes are interconnected and entangled, and the nickel-iron phytate nanoparticles generated by complexation are loaded on the carbon nanotubes.
[0062] Figure 3 TEM image of the catalyst sample prepared in Example 1 of the present invention. Figure 3 It can be seen that the structure of the prepared nanomaterial is that carbon nanotubes are interconnected and entangled, and nickel-iron phytate nanoparticles with an average diameter of about 30 nm are modified on the surface of the carbon nanotubes.
[0063] Figure 6 This is a SEM image of the catalyst sample prepared in Comparative Example 1 of the present invention. Figure 6 It can be seen that the structure of the prepared nanomaterial is that the carbon nanotubes are interconnected and entangled, and the nickel phytate nanoparticles generated by complexation are loaded on the carbon nanotubes. The small number of nickel phytate nanoparticles may be attributed to the relatively weak complexing ability of phytate for nickel ions.
[0064] Figure 8 This is a SEM image of the catalyst sample prepared in Comparative Example 2 of the present invention. Figure 8 It can be seen that the structure of the prepared nanomaterial is that the carbon nanotubes are interconnected and entangled, and the iron phytate nanoparticles generated by complexation are loaded on the carbon nanotubes.
[0065] Example 2 Compared with Example 1, the molar ratio of nickel and iron metal is 9:1. The specific steps are:
[0066] (1) Add 30 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonic to form a uniform carbon nanotube dispersion.
[0067] (2) Dissolve 0.9 mM nickel nitrate hexahydrate and 0.1 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0068] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0069] (4) Dissolve 0.4 mM sodium phytate in 10 mL of deionized water and stir to form a uniform solution; (5) Add the sodium phytate solution into the mixed solution in (3) and stir for 1 hour.
[0070] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0071] Example 3 Compared with Example 1, the molar ratio of nickel and iron metal is 7:3. The specific steps are:
[0072] (1) Add 30 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonic to form a uniform carbon nanotube dispersion.
[0073] (2) Dissolve 0.7 mM nickel nitrate hexahydrate and 0.3 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0074] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0075] (4) Dissolve 0.4 mM sodium phytate in 10 mL of deionized water and stir to form a uniform solution; (5) Add the sodium phytate solution into the mixed solution in (3) and stir for 1 hour.
[0076] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0077] Example 4 Compared with Example 1, the concentration of the aqueous dispersion of carbon nanotubes is 1 mg / mL. The specific steps are:
[0078] (1) Add 20 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonication to form a uniform carbon nanotube dispersion.
[0079] (2) Dissolve 0.8 mM nickel nitrate hexahydrate and 0.2 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0080] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0081] (4) Dissolve 0.4 mM sodium phytate in 10 mL of deionized water and stir to form a uniform solution; (5) Add the sodium phytate solution into the mixed solution in (3) and stir for 1 hour.
[0082] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0083] Example 5 Compared with Example 1, the concentration of the aqueous dispersion of carbon nanotubes is 2 mg / mL. The specific steps are:
[0084] (1) Add 40 mg of carbon nanotubes into 20 mL of deionized water and disperse by ultrasonication to form a uniform carbon nanotube dispersion.
[0085] (2) Dissolve 0.8 mM nickel nitrate hexahydrate and 0.2 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0086] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0087] (4) Dissolve 0.4 mM sodium phytate in 10 mL of deionized water and stir to form a uniform solution; (5) Add the sodium phytate solution into the mixed solution in (3) and stir for 1 hour.
[0088] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0089] Example 6 Compared with Example 1, the molar ratio of phytate to metal salt is 1:2. The specific steps are:
[0090] (1) Add 30 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonic to form a uniform carbon nanotube dispersion.
[0091] (2) Dissolve 0.8 mM nickel nitrate hexahydrate and 0.2 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0092] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0093] (4) Dissolve 0.5 mM sodium phytate in 10 mL of deionized water and stir to form a uniform solution; (5) Add the sodium phytate solution into the mixed solution in (3) and stir for 1 hour.
[0094] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0095] Example 7 Compared with Example 1, the molar ratio of phytate to metal salt is 1:3. The specific steps are:
[0096] (1) Add 30 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonic to form a uniform carbon nanotube dispersion.
[0097] (2) Dissolve 0.8 mM nickel nitrate hexahydrate and 0.2 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0098] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0099] (4) Dissolve 0.3 mM sodium phytate in 10 mL of deionized water and stir to form a uniform solution; (5) Add the sodium phytate solution into the mixed solution in (3) and stir for 1 hour.
[0100] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0101] Example 8 Compared with Example 1, the complexation was stirred for 0.5 h. The specific steps are:
[0102] (1) Add 30 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonic to form a uniform carbon nanotube dispersion.
[0103] (2) Dissolve 0.8 mM nickel nitrate hexahydrate and 0.2 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0104] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0105] (4) Dissolve 0.4 mM sodium phytate in 10 mL of deionized water and stir to form a uniform solution; (5) Add the sodium phytic acid solution into the mixed solution in (3) and stir for 0.5 h.
[0106] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0107] Example 9 Compared with Example 1, the complexation was stirred for 1.5 hours. The specific steps are:
[0108] (1) Add 30 mg of carbon nanotubes into 20 mL of deionized water and disperse them by ultrasonic to form a uniform carbon nanotube dispersion.
[0109] (2) Dissolve 0.8 mM nickel nitrate hexahydrate and 0.2 mM ferric nitrate nonahydrate in 10 mL of deionized water and stir to form a uniform solution.
[0110] (3) Add the metal salt solution into the carbon nanotube dispersion and stir for 5 minutes.
[0111] (4) Dissolve 0.4 mM sodium phytate in 10 mL of deionized water and stir to form a uniform solution; (5) Add the sodium phytic acid solution into the mixed solution in (3) and stir for 1.5 h.
[0112] (6) Centrifugal separation, washing with deionized water and ethanol multiple times, and vacuum drying at 60°C for 12 h to obtain the final sample.
[0113] Fig.10Linear sweep voltammograms of OER in 1M KOH solution for catalyst samples prepared with different nickel-iron metal ratios. It can be seen that the catalytic performance is similar within the above ratio range, but the best is when the nickel-iron metal molar ratio is 8:2.
[0114] Fig.11 Linear sweep voltammograms of OER in 1M KOH solution for catalyst samples prepared at different concentration ranges of carbon nanotube aqueous dispersions. It can be seen that the catalytic performance is similar within the above ratio range, but the best concentration of carbon nanotube aqueous dispersion is 1.5 mg / mL.
[0115] Fig.12 Linear sweep voltammetry curves of OER in 1M KOH solution for catalyst samples prepared with different ratios of phytate to metal salt. It can be seen that the catalytic performance is similar within the above ratio range, but the best is when the molar ratio of phytate to metal salt is 1:2.5.
[0116] Fig.13 The linear sweep voltammetry curve of OER in 1M KOH solution for the catalyst samples prepared in the stirring complexation time range. It can be seen that the catalytic performance is similar within the above ratio range, but the best is when the stirring complexation time is 1h.
[0117] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A method for preparing a carbon nanotube-supported nickel-iron phytate OER catalyst, characterized in that: The following steps are involved: Using water as a dispersion medium, a mixed solution of soluble nickel salt, soluble iron salt and carbon nanotubes is prepared; The sodium phytate aqueous solution is mixed with the mixed solution, and the complexation is carried out by stirring at room temperature. The nickel-iron phytate nanoparticles generated in the complexation process are loaded on the carbon nanotubes to obtain the carbon nanotube-loaded nickel-iron phytate OER catalyst.
2. The preparation method according to claim 1, characterized in that: In the carbon nanotube-loaded nickel-iron phytate nanomaterial, the amount of Ni element used is 70% to 90% of the total molar amount of Ni and Fe.
3. The preparation method according to claim 1, characterized in that: In the mixed solution, the total amount of soluble nickel salt and soluble iron salt and the carbon nanotubes are in a ratio of 0.01 g to 0.02 g: 1 mg to 2 mg.
4. The preparation method according to claim 3, characterized in that: A soluble nickel salt and a soluble iron salt are dissolved in water to obtain a mixed salt solution, and the mixed salt solution is evenly mixed with an aqueous dispersion of carbon nanotubes under stirring to obtain a mixed solution.
5. The preparation method according to claim 4, characterized in that: In the mixed salt solution, the solid-liquid ratio of the total amount of soluble nickel salt and soluble iron salt to water is 0.02g-0.04g:1mL; the concentration of the aqueous dispersion of carbon nanotubes is 1mg / mL-2mg / mL, and the volume ratio of the mixed salt solution to the aqueous dispersion of carbon nanotubes is 1:
2.
6. The preparation method according to claim 1, characterized in that: The molar ratio of sodium phytate: the total amount of Ni and Fe is 1:2-3.
7. The preparation method according to claim 1, characterized in that: The stirring and complexing time is 0.5h to 1.5h. 8 . A carbon nanotube-supported nickel-iron phytate OER catalyst prepared according to the preparation method according to any one of claims 1 to 7 .
9. The carbon nanotube-supported nickel-iron phytate OER catalyst according to claim 8, characterized in that: The carbon nanotubes are interconnected and entangled, and nickel-iron phytate nanoparticles are loaded on the surface of the carbon nanotubes. The average diameter of the nickel-iron phytate nanoparticles is 30 nm.
10. The carbon nanotube-supported nickel-iron phytate OER catalyst according to claim 8, characterized in that: Catalyzes the anodic oxygen evolution reaction under near-infrared light.
Citation Information
Patent Citations
Nickel-iron composite catalyst as well as preparation method and application thereof
CN117966208A
Nickel iron ammonium phosphate electrocatalyst as well as preparation method and application thereof
CN118756194A
Cited By
Catalyst for seawater electrolysis oxygen evolution reaction and preparation method thereof
CN121826785A
A catalyst for electrolysis of seawater oxygen evolution reaction and a preparation method thereof
CN121826785B
Transition metal-based oxygen evolution catalyst as well as preparation method and application thereof
CN122428330A